Profiling nominee directors in Malaysia / Dr. Yang Chik Adam - Adam, Yang Chik (2014)
This paper illustrates the profile of nominee directors in Malaysia's corporate landscape. A nominee director is usually appointed to the board of directors of a company to represent the interests of a specific group or class of persons such as a class of shareholders, a major creditor to the company or an employee group. Section 132(1E) Companies Act 1965 states the responsibility of a nominee director. Under s.132(1E) CA 1965, among others, a nominee director must not subordinate his duty to act in the best interest of the company to his duty to his nominator. Taking into consideration the concentration in Malaysian corporate economy and the joint venture company or incorporated joint venture is a common form of corporate entity in Malaysia, nominee directors independence is put to test. In relation to this profile, the position of nominee directors in various corporate settings will be discussed in terms of their actual and perceived independence from the board of directors that they are in. This paper concludes with an examination of the need for independence when acting as director of a company. It also illustrates that in discharging the duties as director of a company nominee directors must tread the fiduciary duties carefully.